Arbitrase Blockchain dalam Prinsip Kerahasiaan dan Ketidakberpihakan: Lex Digitalis Arbitri - Shiddiq, Naufal; Budhijanto, Danrivanto; Maulana, Mursal (Unram Law Review, 2024)
Kleros blockchain arbitration presents a promising solution for faster, more cost-effective, and more secure arbitration in digital environment. However, it comes with significant challenges; confidentiality and impartiality. Arbitration is often chosen due to its confidentiality. Examining Kleros’ blockchain arbitration, it becomes apparent that the platform lacks of confidentiality regime and therefore raising a number of probable issues. The anonymity of Kleros jurors complicates the matters, makes it challenging to establish trust, legally bind jurors, monitor compliance, and address potential jurors’ misconduct. Additionally, jurors’ anonymity prohibits disclosure of pertinent information, which may  rise  justifiable doubts, thereby resulting in jurors’ impartiality are questioned. Therefore, this article advocates for Kleros to reconsider their strict anonymity policy and to introduce confidentiality and impartiality provisions in order to align more with the established legal practices in digital arbitration environment (Lex Digitalis Arbitri).